Sebuah Studi Eksperimental tentang Pengaruh Periklanan Perilaku Online di Instagram terhadap Niat Beli dan Klik-tayang Konsumen. Mempertimbangkan Peran Moderasi Ukuran Merek dan Peran Mediasi Kepercayaan Merek - Adinda Rania Rezkialsy Barusman (KONTEKSTUAL : Jurnal Ilmu Komunikasi, 2023)
Instagram has released a service called ‘Instagram ads’, which advertises online businesses on Instagram based on their users’ previous online searches. However, it is unknown whether this service would be beneficial for smaller brands. This research aimed to investigate to what extent personalized advertising on Instagram based on consumers’ previous searches affects click-through and purchase intentions, does the effect differ between brand sizes, and can consumers’ level of brand trust explain this difference. A study was conducted using a 2x2 factorial between-subjects design among 139 participants between the ages of 18-28 years old. Findings showed that personalized advertising positively influenced consumers’ behavioural intentions. However, no difference was found between the large brands and small brands. The results also indicated that brand trust could explain the effect of brand size on purchase intention. All in all, this study could help smaller brands decide on whether or not an Instagram ad is worth the investment, fill in the knowledge gaps, and further the research on whether the effects of personalized advertising differ between brand sizes.